Peran Pendidikan IPS dalam Meningkatkan Literasi Perlindungan Konsumen di Era Digital: Studi Literatur - Bayu Aji Saputra Hasibuan; Desy Safitri; Sujarwo (PT. PENERBIT TIGA MUTIARA, 2026)
The advancement of digital technology has transformed consumption patterns while simultaneously increasing risks related to consumer protection, including online fraud, information manipulation, and misuse of personal data, thereby requiring more critical and comprehensive literacy skills. This study addresses the problem of low consumer protection literacy, as indicated by high levels of impulsive consumption behavior, limited understanding of consumer rights and obligations, and an imbalance between the intensity of technology use and the ability to evaluate information effectively. The purpose of this research is to examine the role of Social Studies education in enhancing consumer protection literacy, its integration into the learning process, and the effectiveness of its implementation in the digital era through a literature review approach. The findings reveal that consumer protection literacy remains at a moderate to low level, yet it has a significant relationship with rational economic decision-making and the ability to mitigate digital risks. Social Studies education has been proven effective in improving such literacy through contextual, interactive, and experience-based learning, which strengthens students’ understanding, attitudes, and skills as consumers. The novelty of this study lies in the conceptual and practical integration of consumer protection literacy into Social Studies learning, encompassing cognitive, affective, and behavioral dimensions, as well as emphasizing pedagogical strategies based on case studies and reflective discussions as effective approaches to shaping intelligent and responsible consumers in the digital era.